2003
DOI: 10.1079/bjn2003965
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of dietary alkylresorcinols in ileal-cannulated pigs and rats

Abstract: Alkylresorcinols (AR) are amphiphilic 1,3-dihydroxy-5-alkyl phenolic lipids. AR in food are only found in the outer layers of wheat and rye grains, and in whole grains are present at concentrations of 500-1000 mg/g. In wheat and rye, there are five main homologues, differing in the length of the odd-numbered alkyl chain (from seventeen to twenty-five C atoms long). Because AR may be bioactive, and might serve as biomarkers for these cereals, their absorption was investigated in model experiments with pigs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 23 publications
4
59
2
Order By: Relevance
“…Riboflavin (vitamin B 2 ): 95 % as oral supplement in human subjects (615) Niacin (vitamin B 3 ): low (19) Pantothenic acid (vitamin B 5 ): about 50 % in human subjects for average American diet (616) Pyridoxine (vitamin B 6 ): 71-79 % for an average American diet compared with free compound (616) a-Tocopherol: 70 % in human subjects fed free compound (617) Total ferulic acid: 3·2 -3·6 % urinary excretion in rats (152) Free/soluble-conjugated ferulic acid: at least that of wheat bran in rat small intestine (154) Bound ferulic acid: a small fraction released within small intestine by intestinal esterases (618) Alkylresorcinols: 60-79 % from ileal samples in pigs fed whole-grain rye bread (619) Phytosterols: weakly absorbed from the gut (620) Total free inositols (myo-and chiro-inositol):…”
Section: Appendixmentioning
confidence: 99%
“…Riboflavin (vitamin B 2 ): 95 % as oral supplement in human subjects (615) Niacin (vitamin B 3 ): low (19) Pantothenic acid (vitamin B 5 ): about 50 % in human subjects for average American diet (616) Pyridoxine (vitamin B 6 ): 71-79 % for an average American diet compared with free compound (616) a-Tocopherol: 70 % in human subjects fed free compound (617) Total ferulic acid: 3·2 -3·6 % urinary excretion in rats (152) Free/soluble-conjugated ferulic acid: at least that of wheat bran in rat small intestine (154) Bound ferulic acid: a small fraction released within small intestine by intestinal esterases (618) Alkylresorcinols: 60-79 % from ileal samples in pigs fed whole-grain rye bread (619) Phytosterols: weakly absorbed from the gut (620) Total free inositols (myo-and chiro-inositol):…”
Section: Appendixmentioning
confidence: 99%
“…The study of their micellization in solution is important because in many interfacial processes the performance of the surfactant depends on its concentration and orientation at the interface. On the other hand, it was demonstrated that alkylresorcinols present in daily diet are absorbed by rats, pigs [11], and humans [12,13], and their molecules can incorporate into erythrocyte membranes [14]. Resorcinolic lipids are the group of phenolic lipids with the most precisely defined amphiphilic properties.…”
Section: Amphiphilic Properties Of Phenolic Lipidsmentioning
confidence: 99%
“…Resorcinolic lipids show very low values for the critical micelle concentration (CMC). The CMCs determined for different homologues in neutral pH by solubilization of 1,6-diphenyl-1,3-5-hexatriene were in the range of 4.5-8.5 lM and depended on the length and saturation of the hydrocarbon chains (8), diolefinic (8,11), and tri-olefinic (8,11,14) Fig. 1 The representative structures of selected phenolic lipids.…”
Section: Amphiphilic Properties Of Phenolic Lipidsmentioning
confidence: 99%
“…Studies have reported that the differences in consumption of ARs are due to age but not to body mass index (BMI) because older people change their dietary habits, increasing the amount of whole grain cereal intake (8). It has been estimated that the average daily intake of ARs in free-living population is around 11 mg/day in UnitedKingdom and around 40 mg/day in Finland (9,10), and that 60% of this amount is absorbed (9).…”
Section: Introductionmentioning
confidence: 99%